2018
DOI: 10.1371/journal.pcbi.1006469
|View full text |Cite
|
Sign up to set email alerts
|

An agent-based model for drug-radiation interactions in the tumour microenvironment: Hypoxia-activated prodrug SN30000 in multicellular tumour spheroids

Abstract: Multicellular tumour spheroids capture many characteristics of human tumour microenvironments, including hypoxia, and represent an experimentally tractable in vitro model for studying interactions between radiotherapy and anticancer drugs. However, interpreting spheroid data is challenging because of limited ability to observe cell fate within spheroids dynamically. To overcome this limitation, we have developed a hybrid continuum/agent-based model (ABM) for HCT116 tumour spheroids, parameterised using experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 63 publications
0
42
0
Order By: Relevance
“…Multicellular spheroids represent useful models of many of the microenvironmental characteristics that occur in tumours. Advanced mathematical modelling of these systems can provide key insights into cell proliferation/death, oxygen and nutrient gradients, development of necrosis, and how these compartments interact and change spatially and temporally with spheroid growth and in response to treatment [42]. It has been reported that the anchorage-independent growth conditions of spheroid culture alter glutamine metabolism, favouring reductive carboxylation of glutamine to citrate to support redox homeostasis [43].…”
Section: Discussionmentioning
confidence: 99%
“…Multicellular spheroids represent useful models of many of the microenvironmental characteristics that occur in tumours. Advanced mathematical modelling of these systems can provide key insights into cell proliferation/death, oxygen and nutrient gradients, development of necrosis, and how these compartments interact and change spatially and temporally with spheroid growth and in response to treatment [42]. It has been reported that the anchorage-independent growth conditions of spheroid culture alter glutamine metabolism, favouring reductive carboxylation of glutamine to citrate to support redox homeostasis [43].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of proliferating cells in 3D models is lower than in 2D cultures resulting in greater cellular heterogeneity within the culture [40,41] [42]. It has been reported that the anchorage-independent growth conditions of spheroid culture alter glutamine metabolism, favouring reductive carboxylation of glutamine to citrate to support redox homeostasis [43].…”
Section: Discussion 13mentioning
confidence: 99%
“…There are known advantages of in silico modelling the action of therapeutic agents on known diseases through agent-based modelling 74 . However, the literature evidenced some intrinsic limitations on the choice of parameters, like the size of investigated populations 75 , while major problems are related to model validation 75,76 , also requiring to supplement the models with adequate formal ontologies 77 .…”
Section: Discussionmentioning
confidence: 99%